Belenggu Patriarki dalam Novel Perempuan-Perempuan Harem Karya Fatima Mernissi - Marlina Marlina; Dedi Supriadi; Khomisah Khomisah; Karman Karman (Az-Zahra: Journal of Gender and Family Studies, 2022)
This study discusses the shackles of women, the structure of the work and the author's worldview in the novel Perempuan-Perempuan Harem by Fatima Mernissi. Women's shackles are a limitation of women in obtaining their rights as a woman. The structure of the work is the constituent element of literary works and is often also called the intrinsic element. The structure of the work analyzed in this study includes: Themes, characterizations, plot, setting and point of view. The author's world view is a form of mediation (compromise) between the structure of society and elements of literary works. The method used in this research is descriptive analysis method. Descriptive method of analysis is done by describing the facts and then doing the analysis, The theoretical approach taken is Lucian Goldman's. Analysis of the novel Perempuan-Perempuan Harem by Fatima Mernissi found that there are female shackles, the structure of the work is the theme, plot, characters and characterizations, setting and point of view. The world view of the author that Fatima Mernissi feels as the author of the novel Perempuan-Perempuan Harem is that there are limitations for women in their family environment because they adhere to traditions that limit women's behavior, unlike Moroccan women in general.